Development of a local wisdom-based social media literacy model for K3 behavior in public transport drivers in Padangsidimpuan city, Indonesia - Permayasa, Nayodi; J. Hadi, Anto; Ahmad, Haslinah; Dongoran, Indra Maulana (International Journal Of Community Medicine And Public Health, 2023)
Background: Unsafe driver behavior and driver negligence while driving, one of which is making phone calls while driving a vehicle, can cause traffic accidents and death. Methods: The research design used a quasi-experiment. The research was conducted at the Padangsidimpuan city passenger terminal. The research subject was a public transport driver. Research intervention for 5 months by providing social media literacy modules/guidelines based on local wisdom, leaflets and posters, every month a visit or monitoring of drivers was carried out using a research questionnaire. The research instrument was a research questionnaire used to measure changes in OSH behavior (pre-test and post-test) and the media used were modules, leaflets and posters. Data were analysed by univariate, bivariate, multivariate analysis with SPSS and Friedman test, Mann Whitney test and post hoc test. Results: The results of this study found that at the initial measurement of knowledge with the post 1 measurement, the p value =0.007, the initial measurement with the post 2 measurement p=0.000 and the post 1 and post 2 measurements p value =0.001. This means that there was a significant difference in knowledge between the initial measurement and the post 1 and post 2 measurements. Conclusions: This finding can be concluded that knowledge of safe driving has a greater influence on unsafe behavior compared to years of service.